“I still don’t know how someone gets pregnant”: determinants of poor reproductive health among young female refugees in South Africa - (:unkn) unknown (My University, 2024)
Background: Studies exploring the sexual and reproductive health (SRH) of refugee women have focused primarily on first generation refugees in humanitarian and crisis settings. There is a paucity of research exploring the reproductive health of girls and young women who are born to refugee parents in a host country or who have migrated with their parents at a very young age and who have since reached sexual maturity. We conducted a qualitative study which aimed to explore the reproductive health and rights’ needs and challenges amongst young refugee women in South Africa.Methods The study was carried out in the city of eThekwini (Durban) in South Africa in 2021 and 2022. A total of 35 semi-structured, in person interviews were conducted amongst young refugee women between the ages of 18 and 24 years living in the city centre.Results Twenty-five participants were 17 years or younger on arriving in South Africa, one of whom was born in South Africa. Eleven of these women had experienced one or more pregnancies while living in South Africa and all of these women had experienced at least one unintended pregnancy. Participants had poor reproductive health knowledge of the role of menstruation and how conception occurs. Economic, social, and legal insecurities intersected in complex ways as determinants of poor reproductive health outcomes. Despite availability, contraceptive use was poor and linked to lack of knowledge, myths and unwanted side effects. There were negative economic and social impacts for young refugee women experiencing early pregnancies irrespective of whether they were intended or not. Being unable to conceive or experiencing an unintended pregnancy negatively impacted sexual relationships which were entered primarily for material support. Desire for confidentiality shaped lack of access to legal termination of pregnancy in the public health sector.Conclusion: Participants experienced specific vulnerabilities resulting from their positio
Keywords: African Research